Kajian Roland Barthes Terhadap Makna Dalam Video Klip BTS “Yet to Come” - Salsabila, Jihan; Kholik, Kholik (Innovative: Journal Of Social Science Research, 2025)
This research aims to uncover the layers of meaning contained in the music video "Yet to Come" by the South Korean group BTS through the perspective of Roland Barthes' semiotics. The music video, as a multimodal text, conveys messages not only through the song's lyrics but also through visual elements, symbols, gestures, and cinematic narratives. Utilizing Barthes' theoretical framework, which includes denotation, connotation, and myth, this study explores how various signs in the music video interact and produce more complex meanings for the audience. Employing a descriptive qualitative method, the research aims to identify and interpret the significance of visual elements and how these elements construct a system of signs that conveys specific cultural messages and ideologies. This study contributes to the fields of popular culture, media studies, and the application of semiotic theory in the context of global phenomena. The goal of this research is to provide a deeper understanding of how meaning is constructed in global popular culture products such as K-pop music videos, as well as to demonstrate how Roland Barthes' semiotic theory can serve as a relevant analytical tool in unraveling the complexities of meaning in multimodal texts.